Combined cross-diffusion microbatch method and seeding technique to enhance protein crystallization based on a common dispersing agent. Issue 24 (9th June 2017) - Hou, Hai; Wang, Bo; Xie, Peng-Peng; Guo, Yun-Zhu; Li, Jin; Yin, Da-Chuan
Abstract : We presented a systematic method that combined the cross-diffusion microbatch method (CDM) with the seeding technique to enhance protein crystal reproducibility based on a "common dispersing agent". Abstract : We presented a systematic method that combined the cross-diffusion microbatch method (CDM) with the seeding technique to enhance protein crystal reproducibility based on a "common dispersing agent". The common dispersing agent is used to dilute the crystal seeds. Seven proteins were screened, and more crystallization conditions were found. X-ray diffraction showed that the combined method is practical and useful for obtaining high-quality protein crystals.